Assessing the potential of a Trichoderma-based compost activator to hasten the decomposition of incorporated rice straw - Organo, Nolissa D.; Granada, Shaira Mhel Joy M.; Pineda, Honey Grace S.; Sandro, Joseph M.; Van Hung, Nguyen; Gummert, Martin (Springer, 2022)
The potential for a Trichoderma-based compost activator was tested for in-situ rice straw decomposition, under both laboratory and field conditions. Inoculation of Trichoderma caused a 50% reduction in the indigenous fungal population after 2 weeks of incubation for both laboratory and field experiments. However, the Trichoderma population declined during the latter part of the incubation. Despite the significant reduction in fungal population during the first 2 weeks of incubation, inoculated samples were found to have higher indigenous and total fungal population at the end of the experiments with as much as a 300% increase in the laboratory experiment and 50% during day-21 and day-28 samplings in the field experiment. The laboratory incubation experiment revealed that inoculated samples released an average of 16% higher amounts of CO2 compared to uninoculated straw in sterile soil samples. Unsterile soil inoculated with Trichoderma released the highest amount of CO2 in the laboratory experiment. In the field experiment, improved decomposition was observed in samples inoculated with Trichoderma and placed below ground (WTBG). From the initial value of around 35%, the C content in WTBG was down to 28.63% after 42 days of incubation and was the lowest among treatments. This is significantly lower compared with NTBG (No Trichoderma placed below ground, 31.1% C), WTSS (With Trichoderma placed on soil surface, 33.83% C), and NTSS (No Trichoderma placed on soil surface, 34.30% carbon). The WTBG treatment also had the highest N content of 1.1%. The C:N ratio of WTBG was only 26.27, 39.51% lower than the C:N ratio of NTBG, which is 43.43. These results prove that the Trichoderma-based inoculant has the potential to hasten the decomposition of incorporated rice straw.